The effects of short-duration ischemia and reperfusion on intestinal ganglia in young rats - (:unkn) unknown (My University, 2001)
The etiology of the diseases like Hirschsprung's and intestinal neuronal dysplasia, that shows quantitative and qualitative abnormalities in ganglion cells, is still unclear. Some recent studies suggest that the defect is due to genetic, microenvironmental and ischemic factors. In the present study, we asked whether short-duration ischemia and reperfusion has a reducing role on the amounts of intestinal ganglion cells. Using the hematoxylin and eosin staining and nitro blue tetrazolium dye method of demonstrating NADPH-diaphorase enzyme activity, we examined the distal ileum specimens from 35 young rats for the quantity of ganglion cells. 12 of them had fifteen minutes, 12 of them had thirty minutes of mesenteric ischemia and then reperfusion. Remaining 11 animals served as control group. A 5-cm segment of distal ileum was excised on six to eight postoperative weeks. Both staining methods showed that there is no difference in three groups by means of ganglion cell amounts. In conclusion 15 and 30 minutes of mesenteric ischemia and reperfusion do not have any effects on the ganglion cells. Extension of ischemic period may change these results.
Keywords: Intestinal ganglia; Ischemia-reperfusion; NADPH-diaphorase